Safety and cost analysis of selective histopathological examination following appendicectomy and cholecystectomy (FANCY study): protocol and statistical analysis plan of a prospective observational multicentre study - Willem A Bemelman; Pieter J Tanis; Lianne Koens; Vivian P Bastiaenen; Bartholomeus JGA Corten; Elise AJ de Savornin Lohman; Joske de Jonge; Anne C Kraima; Hilko A Swank; Jaap LP van Vliet; Gijs JD van Acker; Anna AW van Geloven; et al. (BMJ Open)
Introduction Routine histopathological examination following appendicectomy and cholecystectomy has significant financial implications and comprises a substantial portion of the pathologists’ workload, while the incidence of unexpected pathology is low. The aim of the selective histopathological examination Following AppeNdicectomy and CholecystectomY (FANCY) study is to investigate the oncological safety and potential cost savings of selective histopathological examination based on macroscopic assessment performed by the surgeon.Methods and analysis This is a Dutch multicentre prospective observational study, in which removed appendices and gallbladders will be systematically assessed by the operating surgeon for macroscopic abnormalities suspicious for malignant neoplasms. After visual inspection and digital palpation of the removed specimen, the operating surgeon will report whether macroscopic abnormalities suspicious for a malignant neoplasm are present, and if he or she believes additional microscopic examination by the pathologist is indicated. Regardless of the surgeon’s assessment, all specimens will be sent for histopathological examination. In this way, routine histopathological examination can be compared with a hypothetical situation in which specimens are routinely examined by surgeons and only sent to the pathologist on indication. The two main outcomes are oncological safety and potential cost savings of a selective policy. Oncological safety of selective histopathological examination will be assessed by calculating the number of patients in whom a histopathological diagnosis of an appendiceal neoplasm or gallbladder cancer with clinical consequences benefitting the patient would have been missed. A cost analysis will be performed to quantify the potential cost savings.Ethics and dissemination The study protocol was reviewed by the Institutional Review Board of the Amsterdam UMC, location AMC, which decided that the Dutch Medical Research Involving Human Subjects Act is not applicable. In all participating centres, approval for execution of the FANCY study has been obtained from the local Institutional Review Board before the start of inclusion of patients. The study results will be disseminated through peer-reviewed publications and conference presentations. Guidelines will be revised according to the findings of the study.Trial registration number NCT03510923.